Peran Ibu PKK dalam Menurunkan Laju Stunting - Putri Auliya Rohali; Iriani Ismail; Netty Dyah Kurniasari (IPM2KPE, 2023)
This research aims to find out whether the role of the PKK has an effect on reducing the rate of stunting, so within the PKK it has a role in stunting, so within the PKK it has a role in stunting by always coming to the health center or posyandu. The data collection technique used saturated sampling, and the samples used were 50 samples. This approach uses a quantitative approach with data collection methods using questionnaires. The type of data used is primary and secondary. Primary data in this research was obtained from the results of questionnaires that had been distributed to respondents, while secondary data was obtained from several literatures and data from the relevant departments. The data analysis technique used is chi square or chi square using the Statistical Program for Social Science (SPSS) software. Conclusion: Through Chi Square software research, it also shows that there is a relationship between PKK and stunting incidence of 7.936 with ɑ 0.05. Keywords: PKK, Stunting